Role of small polymers in large polymers induced red blood cell adhesion - Rittu Pius Aloor. (2010)
The adhesion of human red blood cells (RBC) to other cells and to surfaces has been of great interest because abnormal adhesiveness of RBC have been linked to the pathophysiology of various diseases associated with vascular disorders. This present study was undertaken to specifically study the effects of small polymers in the RBC adhesion induced by larger polymers. The effects of the coupling of nonadsorbing large and small polymers on the adhesion of RBC to albumin-coated glass was investigated using interference reflection microscopy. Role of small polymers in large polymers induced red blood cell adhesion.